THE CORRELATION BETWEEN STUDENTS’ VOCABULARY AND THEIR DESCRIPTIVE READING COMPREHENSION - Lylys Anita Sarena; Wan Anayati; Andang Suhendi (JOURNAL OF LANGUAGE, 2023)
The study investigates the correlation between students’ vocabulary mastery and their reading comprehension. Reading Comprehension is the ability to read, process it and understand its meaning. It relies on two, interconnected abilities: word reading, being able to decode the symbols on the page and language comprehension, being able to understand the meaning of the words and sentences); meanwhile comprehension is achieved when the reader successfully extracts the useful knowledge from a text and constructs it into a new understandings of their own. The data were collected from 30 tenth grade students. The test items of vocabulary mastery and reading comprehension were given to the students to measure their level of vocabulary mastery and reading comprehension. The results were compared to find out the correlation between those variables. The results show that there was strong correlation between students’ vocabulary mastery and their reading comprehension. The current study concludes that students’ experiences and reading strategies help the students understand text, but vocabulary was more contributive in helping the students to comprehend the texts.